Updating Groundwater Parameter Maps in Eau Claire County - Michalski, Matthew C.; Enderson, Mitch C.; Dowling, Justin A. (My University, 2015)
In this project, we seek to update and improve the publicly available groundwater information in Eau Claire County using higher resolution data and updated methodologies.
Color poster with text and maps.
Keywords: Eau Claire County (Wis.); Groundwater contamination; Groundwater; Posters